Joint Impact Assessment of CTA's support to EAFF (2003-2013) - Wanjiru, Joyce; Gamba, Paul (Technical Centre for Agricultural and Rural Cooperation, 2020)
The report of the in-depth phase of the joint impact assessment of CTA support to the Eastern Africa Farmers Federation (EAFF) is one of the last steps in a series of activities intended to offer an opportunity for evaluating the mutual co-operation between the two institutions.